Bacteria Associated with Arbuscula Mycorrhizal Spores Gigaspora margarita and Their Potential for Stimulating Root Mycorrhizal Colonization and Neem (Melia azedarach Linn) Seedling Growth - SRI WILARSO BUDI; YENNI BAKHTIAR; NUNANG LAMAEK MAY (Microbiology Indonesia, 2012)
Four isolates (BGi1, BGi2, BGi3, and BGi4) bacteria were isolated from surface sterilized arbuscular mycorrhizal fungi (AMF) spores of Gigaspora margarita (Gm). Based on 16S rDNA analyses and phylogenetic tree, it was revealed that isolates BGi1, BGi3 and BGi4 belong to genus Bacillus, whereas BGi2 was very close  to Bacillus megaterium EG 24. Enzymatic activity test showed that all four isolates had cellulase and protease activities; while one isolate (Bacillus sp. BGi4) also has pectinase activity in addition to the celulase  and protease activities. Dual inoculation of Melia azedarch Linn roots by B. megaterium BGi2  and AMF spores G. margarita enhanced mycorrhizal root colonization by 58.3 %. Combination of Bacillus sp. BGi1 and G. margarita increased  height, diameter, shoot biomass, and root biomass of  M. azedarch by  353, 4.8, 4546, and 2810%, respectively,  in comparison to the uninoculated control plant.